PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN HASIL BELAJAR SISWA KELAS X IIS 1 PADA MATERI EKONOMI DI SMA NEGERI 3 SURAKARTA TAHUN PELAJARAN 2014/2015 - Sari, Dewi Tinjung; Kristiani, Kristiani; Wardani, Dewi Kusuma (BISE: Jurnal Pendidikan Bisnis dan Ekonomi, 2015)
The purpose of this research is to improve critical thinking skills and students learning outcomes of economic lesson at class X IIS 1of Senior High Sschool 3 Surakarta in the academic year of 2014/2015 with the implementation of Problem Based Learning (PBL) model. The type of this research is classroom action research. The subject of this research is students at X IIS 1 of Senior High School 3 Surakarta in the academic year of 2014/2015 with 32 students. The procedures of this research are (a) planning, (b) action, (c) observation, and (d) reflection. Based on the research results, the learning process with the implementation of Problem Based Learning (PBL) model can increase the critical thinking skills and learning outcomes of the students. It can be seen in the cycle I that the students’ critical thinking skills in terms of every indicator aspect are pre research 27,1%, cycle I 70,17%, and cycle II 82,52%, and the individual critical thinking skills are pre cycle 16,13%, cycle I 70%, and cycle II 85,48%. Students learning outcomes are also increased at pre cycle have average value 78,41 (percentage of completeness 71,88%), cycle I becomes 82,67 (percentage of completeness 84,38%), cycle II becomes 85,54 (percentage of completeness 93,75%).